Nós propomos! Perspectiva metodológica para o ensino de geografia nos anos finais do ensino fundamental - Hrchorovitch, Gracieli Daiane Gnoatto (2019)
This dissertation is the result of research characterized as a case study developed with 7th grade students (2017) and 8th grade (2018), in Basic Education, at the State School Irmão Isidoro Dumont - Elementary School, located in the city of Itapejara D'Oeste/PR, through the discipline of Geography. The main objective was to analyze the possibilities and the limits of teaching and learning of Geography of the place. The research had a partnership with Representations Group, Spaces, Times and Languages in Educational Experiences – REETLE and the We Proposed Project! It was developed at the University of Lisbon - Portugal, since 2011, by the coordination of Professor Dr. Sérgio Claudino and the State University of the West of Paraná – UNIOESTE/Francisco Beltrão/PR, since 2017. It aimed at the exchange of experiences in the citizenship formation. The problematic question is to think the Geography teaching, through the students’ investigative participation, in the search to form researchers’ beginners and acting in the place where they live. The research development went through 15 phases, developed along two years (2017 and 2018), being: 1) Ethics Committee Authorization ; 2) Identification of the school, of the class(es), of the subjects where the research was coupled; 3) Presentation of the proposal to the Education Secretary of Parana State - SEED / PR; 4) Presentation of the proposal for the students and survey; 5) Project’s theme Definition ; 6) Teams Organization to work ; 7) Choice of name and logo development; 8) Field work planning; 9) Field work realization 10) Diagnostic presentation; 11) Proposals Elaboration by students; 12) Socialization Forum; 13) Self-evaluation of the Project developed by the students, direction and pedagogical team; 14) Report of actions developed and, 15) Elaboration of materials by students. In the theoretical approach the main authors were: both Callai (2005 and 2017), and Cavalcanti (2014 e 2015) discuss the relationship between geographic education and citizenship; Lima; Vlack (2002), reflect the sense and meaning of belonging to the place; Santos (2005 and 2014), conceptualizes the space; in Leontiev; Luria; Vygotskii (2010), present the socio-historical and cultural psychology, valuing the main aspects of child development and the interaction with other individuals and the role of language, Yin (2001), presents the case study, Lacoste (1988), problematizes the ideological manipulations of Geography. The case study arises as a central element and of great methodological importance, by reinforces the development of activities that have proved to be very significant for students and relevant to the local community. By working Geography with a differentiated methodology, it was possible for the students to expand their view in relation to the place. The understanding of geographic space becomes evident with the finalization of the Project because the students acknowledge Geography as the science of the geographic space.